Analisis Kelayakan Usaha Tambak Ikan Nila di Desa Prasung Kecamatan Buduran Kabupaten Sidoarjo - Ryan Mustaqim Kusumah; Parikesit Penangsang (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This tilapia pond business is a business carried out by residents who have empty land / ponds. Tilapia is quite fast in its development from seed to harvest within 4 months. This study aims to analyze several factors ranging from total costs, revenue, income and business feasibility of tilapia fish ponds in Prasung Village, Buduran District, Sidoarjo Regency. There are 3 analytical tools in business feasibility namely R/C ratio, B/C ratio and ROI. This study requires 6 informants of tilapia fish farming business actors. This type of research uses descriptive research. In the research results of 6 tilapia fish pond farmers there is an average total cost of Rp 44,430,833, for an average income of Rp 93,975,000 / occasional harvest, while the average income of Rp 49,544,167 / occasional harvest. Business feasibility analysis tool using R / C whose average of 2.12 means R / C> 1, B / C whose average of 1.12 means B / C> 1, ROI whose average of 86% means ROI> 0%. So the conclusion is that the tilapia pond business is feasible to run.